EP1057 Utilization and timing of Advance Statements on Life-Sustaining Treatment decisions in patients with recurrent gynecologic cancer. (1st November 2019) - Yim, GW; Lee, EJ; Lee, M; Kim, HS; Chung, HH; Kim, J W; Park, NH; Song, YS
Abstract : Introduction/Background: A new legislation on Hospice, Palliative Care and Life-sustaining Treatment Decision (LSTD) has been enforced in Korea since early 2018. This study is to investigate the incidence and timing of LSTD registration among recurrent gynecologic cancer patients. Methodology: Retrospective observational study was performed of patients that were treated for recurrent gynecologic cancer at a tertiary hospital from February 2018 to January 2019. The number, type and the main person to sign the LSTD form, previous number of treatments, time from last treatment to end-of-life (EOL) care decision and time from decision to death were analyzed. Results: Among 1, 162 patients admitted during the study period, 309 patients had recurrent disease. Among them, 51 patients (16.5%) made EOL care decisions by themselves (n=44) or by the family (n=7). In detail, the number of LSTD registration was made in 30 (58.8%) patients during terminal phase and in 19 (37.3%) patients during dying phase and the number of previous advance directives had been documented in only 2 patients (3.9%). Only seven out of 49 patients (14.2%) stated previous knowledge of the new LSTD Act. The majority (92.2%) of patients were in disease progression state, and the median number of chemotherapy regimen was 4 (range 1–9). Among those who have stopped treatment, the median time from the last palliative treatment to LSTD was 42 days (range 7–468). Time from LSTD registration to death was median 10 days (range 0–232). EOL decisions that were made within 3 days of death occurred in 10 patients (19.2%) and most (n=8) of them were surrogate decision-making by the family. Conclusion: The median time from LSTD to death was 10 days. Completion rate of advance directives by the patient was very low. These findings suggest that early patient-family-doctor discussions on LSTD is needed to help patients make advance EOL care decisions. Disclosure: Nothing to disclose